Sufism among Western Academics and Women: Analysis of Distributional Factors - Suratman, Junizar; Meirison, Meirison; Muzakki, M. Harir (The Faculty of Islamic Theology and Humanities, UIN Walisongo Semarang, Indonesia, 2023)
This article examines and explores the phenomenon of Sufism among Western academics and women, as well as the factors that influence it. The background to this study is the increased attention to Sufism after the events of September 11, 2001, in which Sufism was considered an alternative to overcome psychological anxiety in modern life. The aim of this study was to analyze the factors influencing the distribution of Sufism among Western academics and women, as well as to understand the role of women in the spread of Sufism. The research method used is a literature study with a descriptive analysis approach. The main finding of the study is that Sufism is considered a tolerant school and can accommodate a variety of cultures, including in the context of Western culture. The role of women in the spread of Sufism is also very important, where Sufism becomes a means to prevent moral decay and seek spiritual tranquility in the midst of spiritual pressure.